A novel framework for coupled THMC analysis employing explicit rock fracture. Issue 3 (October 2021) - Ogata, S; Maeda, Y; Fukuda, D; Yasuhara, H; Inui, T; Kishida, K
Abstract: A novel coupled thermal-hydraulic-mechanical-chemical (THMC) simulator for fractured porous rock was developed in the present study based on explicit fracture models. This work is an attempt to describe the spatial coupled phenomena sensitive to fracture generation within rock masses by using explicit fracture representation. The simulator was then applied to numerically predict the long-term evolution in the permeability of a rock mass working as a natural barrier within a geological disposal facility of high-level radioactive waste (HLW). The predicted results showed that the fractures generated due to the excavation of the disposal cavity drastically increased the rock permeability around the cavity and that the gradual decrease in permeability with time was caused only within specific fractures where the pressure solution had been activated after the disposal of the waste package into the cavity. The maximum decrease in permeability within the fractures was more than two orders of magnitude. Overall, it was confirmed that the developed simulator can capture the heterogeneous and local permeability evolutions among multiple fractures due to geochemical creep over the long term.